Association of rs2200733 at 4q25 with atrial flutter/fibrillation diseases in an Italian population. Issue 11 (17th October 2008) - Viviani Anselmi, C; Novelli, V; Roncarati, R; Malovini, A; Bellazzi, R; Bronzini, R; Marchese, G; Condorelli, G; Montenero, A S; Puca, A A
Abstract : Background: Atrial fibrillation (AF) and atrial flutter (AFL) are common cardiac conduction disorders affecting many people. Recent studies on sporadic cases of AF/AFL showed a significant association of the single nucleotide polymorphism rs2200733T with the disease, suggesting a genetic factor in the development of the disease. Objectives: To determine the association of rs2200733 with AF/AFL derived from an Italian population sample. Subjects: 78 patients with AF/AFL and 348 controls took part in the study. Design: Genetic case–control study. Results: The results indicate that there is a positive, significant association between the rs2200733 T allele and patients with AF/AFL of Italian origin (allelic p<0.001 with OR = 2.17). Conclusion: These results derived from a sample of the Italian population agree with previously reported findings from an Icelandic study, which also found that the minor allele rs2200733 was associated with AF/AFL disease.